Identifying patterns of retention in care and viral suppression using latent class analysis among women living with HIV in Florida 2015–2017. Issue 1 (2nd January 2021) - Dawit, Rahel; Sheehan, Diana M.; Gbadamosi, Semiu O.; Fennie, Kristopher P.; Li, Tan; Curatolo, Danielle; Maddox, Lorene M.; Spencer, Emma C.; Trepka, Mary Jo
ABSTRACT: The study objective was to classify women with newly diagnosed HIV into patterns of retention in care (≥2 HIV care visits ≥3 months apart) and viral suppression over time and identify factors associated with class membership. Florida HIV/AIDS surveillance data were used to conduct Latent Class Analysis to classify women into patterns, and multinomial regression was used to compare the prevalence of class membership by demographic and clinical factors. Four classes were selected based on model fit parameters: (Class 1) consistently retained and suppressed (>90% probability of being retained and suppressed), (Class 2) not consistently retained or suppressed (≤10% probability of being retained and suppressed), (Class 3) increasingly retained and suppressed, and (Class 4) decreasingly retained and suppressed. The proportion of women in each class was 48.6%, 24.9%, 14.3%, and 12.2%, respectively. Women aged 25–34 compared to 35–49 years old, injection drug use mode of exposure, US born, and not linked to care three months post-diagnosis had a lower prevalence of belonging to the consistently retained and suppressed class. Findings may be useful in tailoring and targeting interventions to increase the prevalence of women who are consistently retained in care and virally suppressed.